Patient Portal, Patient-Generated Images, and Medical Decision-Making in a Pediatric Ambulatory Setting - Ginting, Karolin; Stolfi, Adrienne; Wright, Jordan; Omoloja, Abiodun (Applied Clinical Informatics, 2020)
Background Electronic health record (EHR) patient portals are a secure electronic method of communicating with health care providers. In addition to sending secure messages, images, and videos generated by families can be sent to providers securely. With the widespread use of smart phones, there has been an increase in patient-generated images (PGI) sent to providers via patient portals. There are few studies that have evaluated the role of PGI in medical decision-making.Objectives The study aimed to characterize PGI sent to providers via a patient portal, determine how often PGI-affected medical decision-making, and determine the rate of social PGI sent via patient portal.Methods A retrospective chart review of PGI uploaded to a children's hospital's ambulatory patient portal from January 2011 to December 2017 was conducted. Data collected included patient demographics, number and type of images sent, person sending images (patient or parent/guardian), and whether an image-affected medical decision-making. Images were classified as medical related (e.g., blood glucose readings and skin rashes), nonmedical or administrative related (e.g., medical clearance or insurance forms), and social (e.g., self-portraits and camp pictures).Results One hundred forty-three individuals used the portal a total of 358 times, sending 507 images over the study period. Mean (standard deviation) patient age was 9.5 (5.9) years, 50% were females, 89% were White, and 64% had private insurance. About 9% of images were sent directly by patients and the rest by parents/guardians. A total of 387 (76%) images were sent for medical related reasons, 20% for nonmedical, and 4% were deemed social images. Of the 387 medical related images, 314 (81%) affected medical decision-making.Conclusion PGI-affected medical decision-making in most cases. Additional studies are needed to characterize use of PGI in the pediatric population.
Keywords: patient-generated images; patient portal; electronic health record; medical decision-making